2013
DOI: 10.1017/s204017441300041x
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between polymorphisms and methylation in the H19/IGF2 gene region may contribute to obesity in Mexican-American children

Abstract: Imprinted genes often affect body size-related traits such as weight. However, the association of imprinting with obesity, especially childhood obesity, has not been well studied. Mexican-American children have a high prevalence, approaching 50%, of obesity and/or overweight. In a pilot study of 75 Mexican-American children, we analyzed the relationships among obese/overweight status, methylation status and single-nucleotide polymorphism (SNP) status at a CpG site in a differentially methylated region (DMR) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…3 Polymorphisms of the H19 gene have been demonstrated to alter its expression and are associated with risk factors for cardiovascular and cerebrovascular disease, such as obesity and high blood pressure. [4][5][6][7] H19 is strongly expressed during embryogenesis and subsequently downregulated after birth, but can be reactivated under hypoxic conditions. 8,9 Thus, we hypothesized that H19 might participate in the pathogenesis of ischemic stroke.…”
mentioning
confidence: 99%
“…3 Polymorphisms of the H19 gene have been demonstrated to alter its expression and are associated with risk factors for cardiovascular and cerebrovascular disease, such as obesity and high blood pressure. [4][5][6][7] H19 is strongly expressed during embryogenesis and subsequently downregulated after birth, but can be reactivated under hypoxic conditions. 8,9 Thus, we hypothesized that H19 might participate in the pathogenesis of ischemic stroke.…”
mentioning
confidence: 99%
“…According to Chen et al [32], in women suffering from obesity IGF2 methylation level was lowest in subcutaneous adipose tissue when compared with that in visceral adipose tissue or muscle. While studying Mexican-American lean and obese children Hernandez-Valerio et al [33] found that children with lower IGF2/H19 methylation had higher birth weights than did children with higher methylation. Heijmans et al [34] stated a negative association between H19 methylation and body size.…”
Section: Discussionmentioning
confidence: 99%
“…[140][141][142][143][144][145] A pilot study in 90 obese Mexican-American children showed a significant difference in the frequency of rs10732516 in CpG4 of H19 DMR between obese boys and girls. 146 A higher frequency of CpG4 methylation and a higher frequency of obesity were found among boys than girls. 146 Similarly, higher levels of methylation of H19 DMR was demonstrated in obese infants.…”
Section: Nonhsag044354mentioning
confidence: 97%
“…146 A higher frequency of CpG4 methylation and a higher frequency of obesity were found among boys than girls. 146 Similarly, higher levels of methylation of H19 DMR was demonstrated in obese infants. 147 The CpG4 methylation status may be associated with childhood obesity in a gender-specific manner.…”
Section: Nonhsag044354mentioning
confidence: 97%